Comparison of rule-based tuning for PI controllers / Habib Ahksani Sunario - Sunario, Habib Ahksani (2024)
Proportional-Integral (PI) controller widely used in the industrial process control. It is because due to their simplicity and effectiveness in regulating the system response. However, it depends heavily on proper tuning of its parameter. This study compares various rule-based tuning methods such as Ziegler-Nichols, Cohen-Coon, and Takahashi tuning method to evaluate impact on settling time, overshoot, and system stability. The methodologies then applied to a PI control system, and the simulations conducted to monitor the effectiveness.